Analysis Is The Relationship Of Leader Member Exchange (LMX) Towards Employee Performance Medited By The Employee Commitment - Dewi SHANTY; Triyani TRIYANI; Muhammad SADIKIN; Sarfilianty ANGGIANI (International Journal of Environmental, Sustainability, and Social Science, 2022)
Indonesia is an archipelagic country with a long history as a maritime country. In the past, the maritime archipelago had many kingdoms, such as Sriwijaya, Majapahit, and the kingdoms in Maluku had once held a vital route for world trade through the sale of spices. Merchants from Gujarat and China took herbs and spices from the Maluku Islands and then sent them via merchant ships to China, the Arabian Peninsula, Europe, and Madagascar. Maritime leadership can be defined as the ability of maritime leaders to influence, motivate, and enable others to contribute to the effectiveness and success of maritime organizations. Leader-Member Exchange (LMX) can be a way to promote better leader-follower relationships and, ultimately, improve performance in public sector organizations. Social Exchange Theory (SET) argues that employees can improve performance with high-quality LMX. The purpose of this study was to examine the effect of LMX on organizational commitment and employee performance and to determine the impact of LMX on employee performance by mediating organizational commitment variables. The results prove that LMX affects organizational commitment; LMX has a beneficial effect on employee performance; organizational commitment is significantly positive. Effective LMX is beneficial for employee performance with organizational commitment as a mediating variable